Energy and Environmental Benefit of Solar Charging System for Charging Auto-Rickshaw in Developing Countries - Uddin, Md.; Rahman , A.Z.M.; Mondol, Sumon (The Global Environmental Engineers, 2021)
The energy crisis and environmental impact are the major concern mf the present world. Three-wheeler auto-rickshaw becoming an important passenger transport vehicle in a developing country which are indirectly powered by the grid electricity through the batteries. Such vehicle consumes significant grid energy during charging which increases the load in the national grid and put extra stress on the electrification in line with the environmental impact. This paper investigated the existing facilities for charging auto-rickshaw in Bangladesh and designed a proposed solar charging model as a replacement based on the existing model. Then the energy and environmental benefit were estimated to reflect the significance of the proposed model and contribution in the context of the global energy crisis and environmental impact. The investigation found that the daily energy consumption is 290 kWh for a charging station capacity of 30 auto-rickshaws which is significant. The proposed solar model is designed to meet this demand offset. The environmental analysis showed that the proposed model can offset CO2, CH4, and NOx emissions by 54 tCO2eq, 40 kgCO2eq, and 60 kgCO2eq per year respectively of which the contribution of CO2 is significant. Further research could be focused on the economic and financial analysis in-depth to promote the proposed model.